Analysis Of The Impact Of Love Scam Fraud In The Digital Business World - Syafriana, Rizka (Universitas Muhammadiyah Sumatera Utara, 2025)
The development of technology has changed the way humans interact, and communication in cyberspace has become an important part of everyday life. The internet became the main communication tool for the next ten years starting with the emergence of home computers in the early 1980s. Social networking sites allow users to actively participate in building their social networks, with the media provided to each individual. Since 2019, especially in Indonesia, online dating applications such as Tinder, Tantan, Bumble, and OkCupid have become popular. However, various forms of digital fraud such as love scams have emerged along with the advancement of this technology. This utilizes social networks to deceive victims by claiming a romantic relationship. The normative method is used in this study to analyze the various types of fraud carried out through digital media and the legal consequences resulting from love scams, especially those related to business transactions. Love scams often involve fraud by pretending to be in a romantic relationship to get money, or expand a business, the perpetrator takes advantage of the victim's feelings of wanting to help their partner. Article 378 of the Criminal Code, Article 28 paragraph (1), and Article 45 A paragraph (1) of the ITE Law regulate love scams, however, the differences in norms between these articles create legal uncertainty. However, the ITE Law can be used to prosecute online fraudsters, making it lex specialis in law enforcement.